FAKTOR-FAKTOR YANG MEMENGARUHI STATUS GIZI BALITA RUMAH TANGGA PETANI PADI SAWAH DI DESA KOTADALAM, PESAWARAN - Misma Trimara; Yaktiworo Indriani; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This research aims to analyze the farm income and household income of lowland rice farmers, to evaluate the nutritional status of children under five and to analyze the factors that affect the nutritional status of the children.  This research is located in Kotadalam Village, Way Lima District, Pesawaran Regency involving 32 rice farming families with children aged 13 to 59 months.  The research used a survey method and data collection was carried out in February - March 2020 and analyzed quantitatively, descriptively, and statistically using Seemingly Unrelated Regression (SUR).  The results shows that the average income of lowland rice farmers was IDR16,678,15.63/year, contributed (67.28%) to the household income of IDR 24,791,015.63.  The nutritional status of children under five calculated based on weight/age was mostly in the normal weight category (96.88%), based on the height/age most children was included in the normal category (71.88%) and based on BMI/U, 71.88% included in the category of good nutrition.  Based on the results of statistical tests, the nutritional status based on body weight/age was influenced by maternal nutritional knowledge, energy sufficiency level, protein adequacy level and parenting styles.  Nutritional status based on the height/age was influenced by the mother's nutritional knowledge, the number of siblings, the level of energy sufficiency and the adequacy level of vitamin A.  Children’s nutritional status based on BMI/age was influenced by the number of siblings and the level of protein adequacy.Key words:, household income, lowland rice, nutritional status